Prognostic markers of ferroptosis-related long non-coding RNA in lung adenocarcinomas - Mao, Kaimin; Tang, Ri; Wu, Yali; Zhang, Zhiyun; Gao, Yuan; Huang, Huijing (Frontiers in Genetics, 2023)
Recent studies have focused on the role of ferroptosis in cancers, including lung adenocarcinoma (LUAD), a type of iron-dependent programmed cell death. The factors involved in the regulation of ferroptosis-related genes are still unknown. We analyzed lung adenocarcinoma datasets from the Cancer Genome Atlas (TCGA-LUAD) in this study. We screened 60 ferroptosis-related genes and identified two distinct ferroptosis subtypes. A correlation was found between the expression of certain ferroptosis-related genes and LUAD prognosis. We also screened long noncoding RNAs (lncRNAs) which are co-expressed with 60 ferroptosis-related genes using the Cox single factor analysis and least absolute shrinkage and selection operator (LASSO). Based on a multi-factor Cox regression model that included 13 LUAD ferroptosis-related lncRNAs, we developed a tumor immune cell infiltration-associated risk score model. The risk score model performed well in predicting LUAD outcomes. In addition, we divided TCGA-LUAD tumor samples into two groups based on their risk scores and evaluated the predictability of LUAD tumor risk scores for immunotherapy benefits based on differences in clinical characteristics, tumor mutation burden, and tumor immune cell infiltration. We hope our findings will provide a good basis for future immunotherapy in LUAD.